(untitled) (Marketing Journal, 2025)
The study analyzes the role of artificial intelligence (AI) -based digital marketing strategies in enhancing the efficiency of e -commerce. The importance of AI technologies in improving user experience, personalizing purchasing processes, strengthening secu rity, and optimizing marketing costs is highlighted based on scientific sources and practical examples. The results indicate that AI tools play a significant role in increasing conversion rates, strengthening customer loyalty, and ensuring the sustainable development of trading processes. This work carries both theoretical and practical value for developing strategic approaches in companies.